Plan de comercialización de Productos Lácteos Tanilact para mejorar el nivel de ventas de los distribuidores autorizados en la provincia de Los Ríos periodo 2024. - Molineros Santillán, Mónica Elizabeth (2025)
This study develops a marketing plan to optimize distribution, promotion, and customer loyalty in the company, aiming to enhance its competitiveness in the market. Through a detailed analysis of the current situation, deficiencies were identified in product accessibility, ineffective marketing strategies, and a weak relationship with distributors and retailers. The proposal seeks to address these issues through logistics improvements, the implementation of incentive and promotion programs, and the strengthening of digital marketing to increase brand presence. These strategies are expected to improve product availability in strategic sales points, foster distributor loyalty, and drive sustained sales growth. The project also includes continuous evaluation of the implemented strategies, using key performance indicators to measure their effectiveness. As a result, an increase in operational efficiency, an improvement in brand perception, and greater customer satisfaction are anticipated. In conclusion, this marketing plan provides a comprehensive strategy to strengthen the company’s position in its sector and ensure its sustainable growth in the market.